Сезонные изменения питания утиных на Горьковском водохранилище - Молодовский, А.В. (Вестник зоологии, 1973)
Seasonal character of a nutrition change in the Anatidae 14 species was studied in the lake part of the water storage basin and its Unzhenian and Nemdskian spurs in 1959—1964. Content of 326 stomaches was investigated in adult and young flying birds. The volume of different groups of Anatidae fodder was estimated by sight. The estimation showed that selectivity of fodder in Anatidae of different species is manifested in distinctly expressed seasonal alternation of different groups of food. Abundance and accessibility of most fodder kinds depends on seasonal and annual regularities of their maturation and water level in the water storage basin.